2020
DOI: 10.1590/fst.24119
|View full text |Cite
|
Sign up to set email alerts
|

Determination of some functional and sensory attributes and suitability of colored- and noncolored-flesh potatoes for different cooking methods

Abstract: Twenty-two colored-flesh potatoes and three commercial noncolored-flesh varieties-which were all raw as they were microwaved (800 W, 8 min) and fried (180 °C, 5 min)-were characterized in terms of functional, sensory aspects and suitability for use. Twelve genetic samples were more suitable for frying (> 20% dry matter), four for boiling (~15-18% dry matter) and nine for preparing puree or roasting (~18 to 20% dry matter). The total polyphenol content (TPC) of the raw colored-flesh potatoes contained between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In the case of five cultivars (Herbie 26, Blaue Annelise, Provita, Vitelotte and Bora Valley), the results from the first year of the study were confirmedthe cultivars were in the salad type (A). Cultivar differences in cooking type confirmed by Bienia et al [2020] and Silveira et al [2020].…”
Section: Resultsmentioning
confidence: 80%
“…In the case of five cultivars (Herbie 26, Blaue Annelise, Provita, Vitelotte and Bora Valley), the results from the first year of the study were confirmedthe cultivars were in the salad type (A). Cultivar differences in cooking type confirmed by Bienia et al [2020] and Silveira et al [2020].…”
Section: Resultsmentioning
confidence: 80%
“…Additionally, the antioxidant potential of phenolic metabolites is influenced by the position of hydroxylation [ 23 ] and by the mean relative concentrations of the antioxidants found in the vegetable matrices. Several authors reported that the purple-fleshed varieties were characterized by a high content of antioxidants, and that the content in the pigmented varieties may be 2-3 fold higher than in non-pigmented potatoes [ 5 , 25 ]. This was linked to the high content of polyphenols and anthocyanins, which demonstrated to have strong antioxidant properties [ 7 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several authors reported that the purple-fleshed varieties were characterized by a high content of antioxidants, and that the content in the pigmented varieties may be 2-3 fold higher than in non-pigmented potatoes [ 5 , 25 ]. This was linked to the high content of polyphenols and anthocyanins, which demonstrated to have strong antioxidant properties [ 7 , 25 , 26 ]. Deuber et al [ 27 ] reported that Vitelotte cultivar was characterized by the highest polyphenol and antioxidant content, thus confirming our results [ 23 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Potatoes, as an important source of bioactive compounds (BAC), are highly desirable in the diet, but their chemical composition changes during cooking, which depends on the cultivar, cooking style and conditions [224]. Conflicting results on the effects of cooking on total phenolics and chlorogenic acid content are found in the literature [225,226].…”
Section: Phenolicsmentioning
confidence: 99%